Anthropocentric and Ecocentric: An Application of Environmental Philosophy to Outdoor Recreation and Environmental Education. (September 2015) - Cocks, Samuel; Simpson, Steven
Sometimes environmental philosophers write only for other environmental philosophers, and their insights on the nature–human relationship do not reach environmental educators and adventure programmers. This article investigates one aspect of environmental philosophy and the differences between anthropocentric and ecocentric thinking, and applies it to the outdoor recreation and environmental education fields. Even some philosophers themselves believe that the anthropocentric/ecocentric debate is a theoretical discussion with few practical implications, but there are several reasons that outdoor recreation professionals and environmental educators might consider anthropocentric and ecocentric distinctions in their work. They include an appreciation of motivations behind environmental action and the practical value of discussing philosophical differences.